The Indonesian Government's Efforts to Form Democratic Citizens through Democratic Education - Reviandari Widyatiningtyas; Alek Andika; Warlim Warlim; Ory Syafari Jamel Sutiyan; Adlin Adlin (Universitas of Muhammadiyah Makassar, 2023)
Problems with democracy in Indonesia indicated that citizens do not have a democratic attitude. This research aims to find out the efforts of the Government of Indonesia in shaping democratic citizens through democracy education. The writing of this article used qualitative research methods with an analytical descriptive approach. To obtain data, this research used library studies with library data collection techniques and documentation. The results of this research showed that the government's efforts to form democratic citizens through democratic education are carried out by making educational policies. One of the Government's efforts that is considered effective to form democratic citizens was to integrate Civic Education with democracy education. This is in accordance with the task carried out by Civic Education to form students into democratic and responsible citizens. Through civic education there will be socialization and dissemination of democratic values in society. This is part of the ideals of democracy, one of which is to realize Civic Education as democratic education. Thus it can be concluded that through learning Civic Education, students are expected to be able to develop a democratic attitude.